Elaboración de una guía interactiva en línea sobre el turismo del cantón mejía, dirigido a turistas con la finalidad de difundir la historia y tradición cultural del cantón - Benítez Cuichán, Diego Fernando (2016)
The present investigation was done in Pichincha Province in the Mejia canton, to all of the tourists that visit this beautiful valley, asking about if they know every place in this wonderful town and it permits to get information about cultural and food places that are in Mejia Canton, with the researching was taking account the people opinion, in the surveys done, we could get information and develop the proposal. It consists in an interactive on- line guide which it will visit by tourists for visiting places and go there. It permits that the tourism in the Canton will increase and the tourist can get information easily and fastest about touristic attractive places, restaurants, traditions and cultural parties.